A Novel Approach for Pathway Analysis of GWAS Data Highlights Role of BMP Signaling and Muscle Cell Differentiation in Colorectal Cancer Susceptibility – Erratum. (23rd February 2017) - Mishra, Aniket; MacGregor, Stuart
Abstract : The publishers regret to announce that the affiliation for the above paper was incorrectly inserted. The correct affiliation is below: Aniket Mishra 1, Genetics and Epidemiology of Colorectal Cancer Consortium (GECCO) and the Colorectal Cancer Family Registry (CCFR), and Stuart MacGregor 1 1 Statistical Genetics, QIMR Berghofer Medical Research Institute, Brisbane, Queensland, Australia